Kajian Optimasi Pengangkutan Sampah Kecamatan Cianjur - Iscahyono, Achmad Fauzan; Javani, Adelia Nur; Mukhlis Sudrajat, Habibi Mujahidin; Safitri, Nur Diana (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) ITERA, 2025)
Cianjur District is an area with the largest service scale in Cianjur Regency that requires the most crucial attention, especially in the provision of waste infrastructure. With the increasing population in Cianjur District every year, it is estimated that it will be followed by an increase in the amount of waste that needs to be transported. This study aims to formulate optimal waste transportation in Cianjur District. This study uses a quantitative descriptive method. Optimization of waste transportation is carried out based on an analysis of existing conditions and transportation needs by maximizing working hours to then create a scenario for increasing trips and the number of transport vehicles. The results of this study show that the existing condition of waste transportation in Cianjur District uses the direct individual method with the SCS system which has not been implemented optimally. Therefore, it is necessary to add transport vehicles for waste transportation in Cianjur District every day and increase the number of minimum trips that need to be carried out. If the waste transportation needs can be fulfilled, the level of waste transportation performance in Cianjur District will increase in the future.